A safety-case approach to the ethics of autonomous vehicles. Issue 1 (2nd January 2020) - Menon, Catherine; Alexander, Rob
Abstract: Autonomous Vehicles (AVs) have significant ethical and safety implications. Questions of informed consent and risk acceptance are of primary importance, as is an explicit identification of the ethical principles underlying these decisions. In this paper we present a process framework for producing an ethics assurance case, which can be used to translate ethical imperatives into design decisions and safety management practices. The process and resultant assurance case integrate ethical considerations into the wider engineering lifecycle, providing a tool to demonstrate that design and safety management decisions reflect an identified ethical position.